CRITICAL ACTIVITY IDENTIFICATION OF HALAL ASSURANCE SYSTEM FROM FLAVOR PRODUCTION - Siti Maonah; Dana Santoso Saroso (Operations Excellence: Journal of Applied Industrial Engineering, 2018)
Law No 33 Year 20014 on halal product assurance affecting Indonesian market requirement of a product. Based on this regulation all products marketed in Indonesia must be a halal certified product. Flavor product is categorized as the material which requires halal certificate due to the complexity of the ingredients. Assessment Institute for Food, Drugs, and Cosmetic, The Indonesian Council of Ulama (AIFDC – ICU) taking the role as the halal certification body in Indonesia. Prerequisite program on halal certification is the implementation of Halal Assurance System (HAS). HAS contained eleven criteria, one of them is a written procedure for critical activities. This paper is to identify which stage of production activity that considered as critical activity. A qualitative empirical study performed in this research and the result showed that incoming material, production processes, quality inspection, packing, warehousing, and distribution are the critical activity in halal certified flavor production. Written procedure for critical activities cannot stand alone, this criteria is related to HAS criteria number four and six, material and production facility.